An Illustrative Case of Subcutaneous Panniculitis-Like T-Cell Lymphoma - Farshad Bagheri; Kelly L. Cervellione; Belkis Delgado; Luis Abrante; Jose Cervantes; Jitendra Patel; Alan Roth (Journal of Skin Cancer)
Subcutaneous panniculitis-like T-cell lymphoma (SPTCL) is a very rare form of skin lymphoma that is localized primarily to the subcutaneous adipose tissue without palpable involvement of the lymph nodes. Diagnosis of SPTCL is a challenge, especially during its early phases when symptoms mimic other, more common conditions, such as benign panniculitis, eczema, dermatitis, psoriasis and cellulitis. Clinical and systemic features are nonspecific and can include fever, chills, and weight loss. Further complicating diagnosis is the high number of false negatives provided by biopsy. Here we present a case of SPTCL that illustrates the full course of the disease, from presentation and multiple misdiagnoses to correct disease recognition and successful treatment. A review of the challenges of diagnosis is provided with recommendations for more accurate and timely recognition of SPTCL.